Hubungan Supervisi Akademik dan Kompetensi Sosial Emosional dengan Kinerja Guru di SD Negeri Kecamatan Kota Masohi Kabupaten Maluku Tengah - Mahulauw, Emy; Kempa, Rudi; Rumfot, Sumarni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The quality of education is considered low by many groups. One of the factors that influence this is the ability of teachers as educators. The enthusiasm for teacher performance is influenced by several factors, including the academic supervision of supervisors, school principals, and the social emotional influence of school principals. This study aims to, describe the relationship of school academic supervision. This research is a quantitative descriptive research. Samples were obtained from 90 teachers at 14 public elementary schools in Kota Masohi District. The technique used is a closed questionnaire. The method used is data analysis. The results of the analysis show that: School academic supervision is in the moderate category (83%), Socio-emotional competence is in the category (76%), Teacher performance is in the moderate category (82%). There is a positive and significant relationship between the academic supervision of school supervisors, social emotional competence and teacher performance so that H0 is rejected and H1 is accepted. Conclusion of school academic supervision, Teacher social emotional competence with the performance of teachers of 14 public elementary schools in Masohi City, It still has to be done optimally to achieve the target of supervision. Suggestions from the results of this study the supervision of school academic supervisors and teachers' social emotional competence involves teachers actively in the process of implementing and developing programs, and making decisions related to the development of teacher performance competencies.